2009
DOI: 10.1002/ar.20972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Long Bone Surface Textures as Ontogenetic Indicators in Centrosaurine Ceratopsids

Abstract: The search for criteria for aging non-mammalian fossil vertebrates has preoccupied paleobiologists in recent years. Previous studies of the long bones of pterosaurs and modern and subfossil birds as well as of cranial material of centrosaurine ceratopsid dinosaurs have documented variations in surface textures that seem to be ontogenetically related. In this study, long bones from the centrosaurine ceratopsid genera Centrosaurus, Einiosaurus, and Pachyrhinosaurus are examined to test the hypothesis that change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Comparative study of skeletal development of major limb bones in the postnatal ontogeny of five modern birds showed a consistent pattern of ontogenetic transition of surface textures, as well as interspecific variation in the relative timing of transitions. Histological observations, combined with morphometric examination published elsewhere (Watanabe, ), revealed that rough surface textures are indicative of the active circumferential growth of long bones, confirming the relationship between surface textures and growth regimes (Tumarkin‐Deratzian et al, ; Tumarkin‐Deratzian, ). The active circumferential growth of long bones generally persists after the time of fledging, and seems to cease before the time of sexual maturity, although the exact timing of the cessation is not clear (Watanabe, ).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Comparative study of skeletal development of major limb bones in the postnatal ontogeny of five modern birds showed a consistent pattern of ontogenetic transition of surface textures, as well as interspecific variation in the relative timing of transitions. Histological observations, combined with morphometric examination published elsewhere (Watanabe, ), revealed that rough surface textures are indicative of the active circumferential growth of long bones, confirming the relationship between surface textures and growth regimes (Tumarkin‐Deratzian et al, ; Tumarkin‐Deratzian, ). The active circumferential growth of long bones generally persists after the time of fledging, and seems to cease before the time of sexual maturity, although the exact timing of the cessation is not clear (Watanabe, ).…”
Section: Resultssupporting
confidence: 76%
“…A common method of ontogenetic ageing for vertebrate bones is the one based on the inspection of bone surface texture (textural ageing; Tumarkin-Deratzian et al, 2006, 2007Tumarkin-Deratzian, 2009). Textural ageing relies on transitions of bone surface textures in (postnatal) ontogeny, which reflects ontogenetic variation of histological structures of the bone matrix underlying the surface, and ultimately bone growth rate.…”
mentioning
confidence: 99%
“…9A). A frayed surface in section may also be associated with long-grained bone texture in juvenile dinosaurs (Tumarkin-Deratzian et al 2006;Brown et al 2009;Tumarkin-Deratzian, 2009).…”
Section: Frayed Bone Marginmentioning
confidence: 99%
“…Size classes within a bonebed of a single species, surface texture of bones, or degree of suture closure are examples of tools often used to estimate relative age and ontogenetic status of fossil animals, but these methods are always highly imprecise (e.g. [1] [4] ). The study of bone histology has enabled paleontologists partially filling this methodological gap, because its insights can provide the required absolute data in many cases (see e.g.…”
Section: Introductionmentioning
confidence: 99%